Small, spontaneously ruptured gastrointestinal stromal tumor in the small intestine causing hemoperitoneum: A case report. (2017) - Fukuda, Shuichi; Fujiwara, Yoshinori; Wakasa, Tomoko; Inoue, Keisuke; Kitani, Kotaro; Ishikawa, Hajime; Tsujie, Masanori; Yukawa, Masao; Ohta, Yoshio; Inoue, Masatoshi
Graphical abstract: Highlights: Hemoperitoneum is a rare and potentially life-threatening complication of GISTs. Even small GISTs in the small intestine can rupture and cause hemoperitoneum. Because of their high vascularity, ruptured GISTs can cause massive hemoperitoneum. Abstract: Introduction: Gastrointestinal stromal tumors (GISTs) are clinically asymptomatic until they reach a significant size; therefore, GISTs that are 2 cm or less are typically asymptomatic. Patients with symptomatic GISTs typically present with abdominal pain, gastrointestinal bleeding, or a palpable mass but rarely present with hemoperitoneum. Presentation of case: A 72-year-old Japanese man presented to us with acute onset abdominal pain. Physical examination showed peritoneal irritation in the lower abdomen. Findings of abdominal computed tomography were suggestive of hemoperitoneum; therefore, urgent surgery was performed. Approximately 1500 ml of blood in the abdominal cavity was removed. A small, ruptured mass was found in the middle of the small intestine, and partial resection of the small intestine, including the mass, was performed. The resected tumor was 2 cm in size and exhibited an exophytic growth pattern. Immunohistochemical staining revealed that the tumor was positive for KIT and CD34; therefore, a final diagnosis of GIST was made. Treatment with imatinib at 400 mg per day was started from postoperative month 1. The patient is doing well without recurrence 5 months after surgery. Discussion: Even small GISTs in the small intestine can spontaneously rupture and cause hemoperitoneum. Moreover, when a patient presents with sudden abdominal pain and hemoperitoneum without an evident mass on imaging, clinicians should be aware of the possibility of bleeding from a small GIST in the small intestine. Conclusion: We present an extremely rare case of a patient with a small, spontaneously ruptured GIST in the small intestine, resulting in hemoperitoneum.